Fine Motor Function in Breast Cancer: Special Focus on Sensation - AKEL, BURCU SEMİN; EVRENDİLEK, HALENUR; HOŞBAY, ZEYNEP (Springer Nature, 2025)
After cancer treatment, women with breast cancer often experience immediate impairment in fine motor function. This can be due to chemotherapy-induced peripheral neuropathy (CIPN), muscle weakness or protective posture, lymphedema, fatigue, and stress. The loss of hand dexterity and sensory dysfunction can significantly influence the ability of cancer patients and survivors to function at work and at home. Unfortunately, this adverse effect in daily life may generally be overlooked while focusing on primary treatment for survival. Assessing somatosensory and fine motor skills is crucial for planning early intervention in the early stages of breast cancer. Education, including self-management strategies, exercise, and sensorimotor training, are the main methods for addressing sensory disturbances and fine motor skill impairment. Although the benefits of these methods are acknowledged, the strongest evidence is found only for physical exercise. Further research is needed to identify the most effective exercise modalities, optimal timing, and duration of interventions.
Keywords: Fine Motor Skills; Hand Dexterity; Peripheral Neuropathy; Sensation; Somatosensory Training